If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15p + 15q + p + -6q + -5p = 0 Reorder the terms: 15p + p + -5p + 15q + -6q = 0 Combine like terms: 15p + p = 16p 16p + -5p + 15q + -6q = 0 Combine like terms: 16p + -5p = 11p 11p + 15q + -6q = 0 Combine like terms: 15q + -6q = 9q 11p + 9q = 0 Solving 11p + 9q = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-9q' to each side of the equation. 11p + 9q + -9q = 0 + -9q Combine like terms: 9q + -9q = 0 11p + 0 = 0 + -9q 11p = 0 + -9q Remove the zero: 11p = -9q Divide each side by '11'. p = -0.8181818182q Simplifying p = -0.8181818182q
| 9y+5=6y-4 | | 9x-16-8x+16=-3 | | 7m+4n-3m+8n= | | 5x+8x+4y+2y= | | x^4+16i=0 | | -5x+8y-4= | | 3x=-80 | | 53-3x=11-10x | | (2x-1)(x+1)=0 | | 14+4(x+1)=26 | | (2x-1)x(x+1)=0 | | 2a+30=50 | | 3x(4x-5)+3=0 | | 5x^2+3x-28=0 | | 10x^2+0.2x+200=0 | | v=axt | | 20x+12y-28= | | 5d-30+40= | | -5y+-15= | | 160=(2w+14)w | | x^3=40 | | 24x+16=19 | | 7r+56= | | 7r+8= | | 3b-6-12b-7= | | -8(2t+9)=-168 | | 4(f-5)=-4 | | (x+4)(3-5x)=6-3(x-1) | | (5x-10)=6x+5 | | -(3x-7y+1)= | | x=1287.4(17)+48470 | | 2(x-10)+(x-10)=46 |